A pilot study of a novel specs for chronic dizziness. (3rd June 2018) - Gordon, C. R.; Tamir, R.; Furas, R.; Klein, C.; Roth, R.
Abstract : Objective: A pilot study to assess the efficacy and safety of a novel specs device developed to alleviate chronic dizziness using eyeglasses with referential marks fixed on the lenses. Materials and methods: Forty patients with stable symptoms of chronic dizziness for more than 3 months participated in a 4‐week, double‐blind, randomized treatment with Active‐Specs or Sham‐Specs. Efficacy was assessed using validated semiquantitative scales and questionnaires of vertigo, dizziness and anxiety. Safety evaluation included monitoring of any adverse event. Results: Thirty‐six participants were included in the efficacy analysis, 18 in each group. Twelve of 18 subjects (67%) treated with Active‐Specs reported substantial improvement of symptoms compared to six (33%) with Sham‐Specs showing a significant improvement on Clinical Global Impressions scale ( P = .017). The Active‐Specs group showed significant reduction in the Vertigo Visual Analogue Scale ( P = .017) and a nonsignificant but consistent trend of improvement measured by the Dizziness Handicap Inventory and Beck Anxiety Inventory. There were no adverse events related to the treatment. Conclusions: This novel specs device seems to be a safe and promising novel treatment for chronic dizziness. We hypothesize that marks in specific zones of the peripheral visual field could strengthen information of real head motion counteracting the mismatch sensory and locomotor information causing chronic dizziness. The results of this pilot study should be followed up by additional studies aimed at confirming the present encouraging findings.